Espaços de melodias negras em Aquarius, de Kleber Mendonça Filho - Ribeiro, Luís Henrique Marques (2020)
This research in cinema and analysis of fictional discourse, studies the relationship between fiction and society of issues related to racism, memory and urban space based on the structuring of the cinematic narrative of the Brazilian film Aquarius (2016), by Kleber Mendonça Filho. For this, we used a theoretical framework on memory, from Ricoeur (2007), Candau (2011) and Halbwachs (1990) category of fictional space and character, from Lins (1976), Borges Filho (2007), Brandão (2013), Reis and Lopes (1988); identity, with Hall (2015); racism, from Fernandes (2008a, 2008b), hooks (2019), Munanga (2017), Schwarcz (2017, 1998), Stam (2008), among others. The research results indicate, that the use of the space category is fundamental in the development of the narrative, as well as the observation of racism, as constitutive of the Brazilian social formation, is a key piece in understanding the layers of the main character, Clara, and her relationship with the character Ladjane, her maid. It was possible to identify the prevalence of memory through the use of urban space, as fundamental means in the construction of racism in the film. This was identified through speeches, of the characters, mise-en-scene, photographs and objects that make up the space. The film is attentive to the use of these relationships and therefore identifies a continuity of Brazilian social themes in the director's work. However, the articulation of these themes is constructed in a subtle and synthesized way, which requires an attentive and trained eye, capable of interpreting the multiplicity of diegetic information in the mise-en-scene